Strategy of Implementing Automated Identification System -ITS in Port Systems - Jolić, Natalija; Šimić, Mato; Brnadić-Zoranić, Sanja (Promet - Traffic&Transportation, 2003)
Careful consideration of the intelligent transport systems -ITS, shows that the efficiency of ITS solutions is reflected in thetechnologies introduced in the recent information age. Today,it i.s possible to collect, analyse and undertake various activitiesbased on the data and infOimation, that had not been possiblebefore. The technological development in sensor technologyand devices for data collection allow almost immediate,real-time analysis of information and simultaneous performanceof feedback activities that are so fast that they can contributeto the functioning and operation of the transportationsystems.